2021
DOI: 10.1007/s10549-021-06306-4
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II trial of ruxolitinib in combination with trastuzumab in metastatic HER2 positive breast cancer

Abstract: Purpose: Preclinical data demonstrate STAT3 as an important regular in HER2+ tumors, and disruption of the IL6-JAK2-STAT-S100A8/S100A9 signaling cascade reduces HER2+ cell viability. Ruxolitinib is an FDA approved inhibitor of JAK1 and JAK2. We performed a phase I/II trial investigating the safety and e cacy of the combination of trastuzumab and ruxolitinib in patients with trastuzumab-resistant metastatic HER2+ breast cancer.Methods: Patients with metastatic HER2+ breast cancer progressing on at least 2 lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…However, the combination of the JAK2 inhibitor ruxolitinib with trastuzumab for the treatment of patients with pretreated metastatic disease was studied in a phase 1/2 clinical trial and showed no improvement of outcomes, compared to historical controls. Additional research is needed to determine if there is a role for other JAK/STAT targeting agents, and the optimal setting [ 82 ].…”
Section: Mechanisms Of Resistancementioning
confidence: 99%
“…However, the combination of the JAK2 inhibitor ruxolitinib with trastuzumab for the treatment of patients with pretreated metastatic disease was studied in a phase 1/2 clinical trial and showed no improvement of outcomes, compared to historical controls. Additional research is needed to determine if there is a role for other JAK/STAT targeting agents, and the optimal setting [ 82 ].…”
Section: Mechanisms Of Resistancementioning
confidence: 99%
“…These data suggest that the currently approved doses of ruxolitinib may be insufficient to achieve the potent inhibition of the IL-6/JAK/STAT pathway necessary to induce clinically meaningful responses, and that either novel drug-to-target delivery mechanisms are needed to bypass systemic toxicity (thus allowing higher doses to be given safely), or more specific JAK inhibitors need to be tested to minimize off-target toxicity while maximizing on-target suppression. Our results add to the growing body of evidence that utilizing ruxolitinib in different MBC settings (ER+ 15 , HER2+ 17 , and triple negative 14 , 16 ) is not effective, which may be explained in part by sub-optimal suppression of the JAK/STAT pathway.…”
Section: Discussionmentioning
confidence: 50%
“…Despite strong pre-clinical rationale for IL-6/STAT3 blockade, early phase studies utilizing ruxolitinib (INCB018424), an orally available selective JAK1/2 inhibitor currently approved by the Food and Drug Administration (FDA) for use in myelofibrosis, polycythemia vera, and graft-versus-host disease 13 have failed to show clinically meaningful responses in metastatic breast cancer as a single agent 14 or in combination with chemotherapy 15 , 16 or trastuzumab 17 . However, no studies to date have examined its feasibility and activity in combination with endocrine therapy in the ET-resistant metastatic setting.…”
Section: Introductionmentioning
confidence: 99%
“…This type of response is also consistent the lack of efficacy of ruxolitinib as a single agent in solid tumors [ 27 , 28 ]. A recent study demonstrates that addition of ruxolitinib to trastuzumab did not improve response in heavily pretreated patients [ 29 ]. These clinical findings are consistent with the notion that the TG2:NF-κB:IL6:STAT3 loop is operant during acquisition of resistance, and targeting this pathway is incapable of re-sensitizing tumors that have already bypassed HER2 signaling via alternative growth factor pathways.…”
Section: Discussionmentioning
confidence: 99%